Lead Chemistry - Chooto, Pipat (IntechOpen, 2020)
Lead continues to amaze us in a variety of ways. The more we learn, the more we are amazed, or more like it, obsessed! Even though we might think that we know the element quite well, the fact is that more research must be conducted to support its subtle behaviors and effects. The most obvious aspect is the effects of lead on health. Because lead is still in use today, we have to understand the effects of lead on our metabolisms. In addition, more and more compounds of lead have been continuously synthesized and their properties and behaviors are required with the help from a variety of scientific disciplines. To provide information for newcomers, especially students or even the public, the overview of lead effects has been included in this book. Despite the variety of lead aspects the book might seem to contain, at least some topics should suit readers? interests. The rest, meaning the contents for new books, depends on how fast you can take the benefits out of this book!